2019
DOI: 10.1002/ajhb.23251
|View full text |Cite
|
Sign up to set email alerts
|

Are there gross motor coordination spurts during mid‐childhood?

Abstract: Objectives: The aims of this study were (1) to identify the timing of the midgrowth spurt (MGS) in stature in children and (2) to identify gross motor coordination (GMC) spurts when aligned by the age of attainment of the MGS (aMGS). Methods: Stature, weight, and GMC were measured in 245 Portuguese children followed annually from 6 to 10 years. GMC was assessed and to estimate children's MGS in stature as well as GMC spurts in each of the four tests aligned by aMGS, we used a nonsmoothed polynomial methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In contrast to the study by Lopes et al (), which suggests alterations in the association between adiposity indicators and motor coordination according to sex in young children from 9 to 12 years old, the present study shows that the associations found are independent of the child's sex. According to Malina, Bouchard, and Bar‐Or () are not expected morphology differences between boys and girls in preschool age, as well as gains in stature are similar throughout early childhood (Santos et al, ). However, the age group investigated by Lopes et al () may be involved in changes from biological maturation, which was not controlled in the study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the study by Lopes et al (), which suggests alterations in the association between adiposity indicators and motor coordination according to sex in young children from 9 to 12 years old, the present study shows that the associations found are independent of the child's sex. According to Malina, Bouchard, and Bar‐Or () are not expected morphology differences between boys and girls in preschool age, as well as gains in stature are similar throughout early childhood (Santos et al, ). However, the age group investigated by Lopes et al () may be involved in changes from biological maturation, which was not controlled in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, this methodology was used by Yag€ ue and De La Fuente (1998) in Spanish boys and girls, and by Philippaerts et al (2006) in Belgian male soccer players. A more general approach of this methodology was developed and previously used by Dos Santos et al (2019) in Portuguese boys and girls, as well as by Silva et al (2019) in Brazilian boys and girls.…”
Section: Statistical Proceduresmentioning
confidence: 99%
“…This generalization was successfully applied to identify spurts in children's gross motor coordination. 20 Graph pad Prism v8 software was used to produce all figures.…”
Section: Discussionmentioning
confidence: 99%
“…A generalization of the methodology was developed by a University of Porto mathematician, who also developed the software to conduct all analyses. This generalization was successfully applied to identify spurts in children's gross motor coordination 20 . Graph pad Prism v8 software was used to produce all figures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation